PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN SOSIOLOGI - Susanti, Aprida Dewi; Zakso, Amrazi; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is "The Effect of Talking Stick Learning Model to Students? Learning Outcomes on Sociology Subject in SMA Islam Bawari Pontianak". The problems of this research were, what are the steps to use talking stick learning model on students? learning outcomes on the sociology subject at class XI IPS 2 in SMA Islam Bawari Pontiana, How is the learning outcome after using talking stick learning model on sociology subject at class XI IPS. The method in this research was quasi experimental research, with the nonequivalent control group design. Data collection was done through direct observation technique and measurement technique. The data tools used were multiple choice test and observation sheet. The results research in implementation steps was prepared based on the lesson plan. The second observation, the observer?s experimental class became more critical and active from the control class, and at the stage of using the sticking learning model could be seen the post-test results. The mean score of post-test of the experimental class was 80.24, while the control class was 76.63. It was proved by the measurement which showed the effect size 0.43 indicating moderate level or. Keywords: Talking Stick Learning Model, Learning Outcomes.